Arab Community Encounter with Kaili Culture in Education and Da’wah - Syakir Mahid; Andriansyah Andriansyah; Ismail Suardi Wekke (el Harakah: Jurnal Budaya Islam, 2018)
This article identifies the Islamic education movement and da’wah (Islamic missionary endeavor) of the Arab community in Palu incorporated in the Alkhairat organization. The formation of this organization arose from a madrasah (madrassa) named “Madrasah Alkhairat Al-Islamiyah” found by Sayyid Idrus bin Salim Aljufri, an ulama (Islamic scholar) from Hadramaut, in 1930 in Palu. The formation of the madrasah was the response of the Arab community in Palu Valley to the Christianization of Dutch Christian missionaries under the auspices of the Leger Dois Heist (Salvation Army). This study uses non-participant observation methods and purposive in-depth interviews with ten subjects consisted of leaders, teachers and staffs in Alkhairat to obtain data related to the topic. Furthermore, the authors verify the data. Finally, this article shows that the Islamic education and da’wah movement undertaken by the Arab community in Palu Valley reflects the process of integration and harmonization of Arabs with local people, and has supported the construction progress in Palu.Artikel ini mengidentifikasi gerakan pendidikan dan dakwah Islam komunitas Arab di Palu yang tergabung dalam organisasi Alkhairat. Terbentuknya organisasi ini berawal dari sebuah madrasah bernama “Madrasah Alkhairat Al-Islamiyah” yang didirikan oleh Sayyid Idrus bin Salim Aljufri, seorang Ulama asal Hadramaut, pada tahun 1930 di Palu. Pembentukan madrasah tersebut merupakan respon komunitas Arab di Lembah Palu terhadap kristenisasi yang dilakukan oleh para misionaris kristen Belanda di bawah naungan Leger Dois Heist (Bala Keselamatan) terhadap masyarakat Palu dan sekitarnya. Penelitian ini menggunakan metode observasi non-partisipan dan wawancara mendalam terhadap sepuluh orang yang terdiri pimpinan, guru maupun staff dalam jaringan Alkhairat guna mendapatkan data terkait topik yang dikaji. Selanjutnya, penulis melakukan verifikasi data yang dijadikan bahan dalam penulisan. Akhirnya, artikel ini menunjukkan bahwa gerakan pendidikan dan dakwah Islam yang dilakukan oleh komunitas Arab di Lembah Palu mencerminkan proses integrasi dan upaya harmonisasi orang-orang Arab dengan masyarakat lokal setempat serta telah mendukung perkembangan pembangunan di Kota Palu.